HERESIOLOGI PARA PERAWI HADIS Desakralisasi Penilaian Kritikus Hadis Dalam Jarh wa Taâ€™dil - Nabiel, Muhammad (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2018)
In the tradition of scholarly criticism of hadith, the narrative pathway obtained from the heretical narrators is a hotbed of debate among muhadditsin. There are three classes related to whether or not to accept the narratives of heretical heretics. The first group views the absolute narration of hadith from them in absolute terms. The second group considers it possible to narrate the hadith from the heretical narrator absolutely as long as it maintains the proportionality and credibility of the transmission. While the third group is more moderate than the previous group. There are certain conditions to be made regarding this issue. One of them, he is not propagandis over bid'ah it. From this we can see that the term 'justness' as a prerequisite of authentic hadith in the perspective of ahl al-sunnah needs to be reviewed. Departing from the above classification, this paper focuses attention on the concept of the 'narrators' and its relation to the controversy surrounding the acceptance of the traditions of ahl al-bid'ah. Keywords: Bid'ah, Jarh and Ta'dil